Lipid profile and its relevance in carcinoma breast - Rohariya, Hrituraj; Gharde, Pankaj; Gharde, Pramita Muntode (International Surgery Journal, 2017)
Background: Breast cancer has emerged as a rapidly growing cancer in India and has already replaced cervical cancer. According to global cancer statistics for the year 2008, breast cancer resulted in 46 million deaths. In Asia, incidence rate of breast cancer is lower but is drastically rising. Nevertheless, while dyslipidemia [high LDL-C (low density Lipo-protein-cholesterol) and low HDL-C (high density lipo-protein-cholesterol) levels] has controversial role in this disease; the specific influence of dyslipidemia in breast cancer initiation and progression is not completely understood. So, we undertook this study. Methods: The study was conducted in the department of general surgery, at Medical College and allied Hospital, in Central rural India between year 2012 and 2014. It was a case control study with a sample size of 50 female participants attending the surgery in patient department, fitting in the inclusion criteria as cases and 50 matching controls. The Data was entered in master chart was statistically analyzed by using SYSTAT version 11 and tests were applied accordingly. Results: Age is a crucial factor in malignancy, most of the studies show malignancy presents more in elder population when compared to young ones. In most patients were between 31-50 years. The youngest patient was of 36 years and the oldest was 78 years. The mean age of the patients affected was 48.54 years which is close to the values in other studies. This study also demonstrated significantly high (p value<0.01) serum TC (total cholesterol) levels of post-menopausal study group (32%, more) as compared to post-menopausal control group. The increase in Serum TC levels was more in post-menopausal study group as compared with pre-menopausal study group. Present study had not shown a significant difference (p value >0.05) between serum levels of HDL-C levels in pre-and post-menopausal control group and study group, though post-menopausal cases had slightly lower values of HDL-C when compared with pre-menopausal controls. Conclusions: We conclude from this study that there is a definite positive correlation between carcinoma breast and fasting lipid profile. The pre-and post-menopausal cases showed significant correlation as far as Total Cholesterol and LDL. Whereas there was no significant correlation between HDL, VLDL and TG (triglycerides). Body mass index has no relation with carcinoma breast.